Ambidextrous strategy and execution in entrepreneurial project-oriented organizations: The case of Pagani supercars. Issue 1 (January 2021) - Di Muro, Paolo; Lecoeuvre, Laurence; Turner, Rodney
Highlights: This research explores the dynamics underpinning the interplay of strategy and execution in entrepreneurial project-oriented organizations when an ambidextrous logic is applied. The empirical findings are the result of an explorative longitudinal research on supercar maker Pagani Automobili in the period 2007–2019. Three integrative mechanisms are suggested to describe the ambidextrous management of the interplay within and between strategy and project levels. The work also recognizes the critical role of projects in entrepreneurial environments and suggests that the accomplishment of ambidexterity is unique in nature as it is aimed at reconciling the uniqueness of competitive propositions and that of projects within a unique entrepreneurial environment. Abstract: This research explores the dynamics underpinning entrepreneurial project-oriented organizations. Specifically, it focuses on how strategy and execution by projects are managed and how ambidexterity – a firm's ability to exploit old certainties while exploring new possibilities – operates as a logic. The empirical findings from an explorative longitudinal research of supercar maker Pagani Automobili in the period 2007–2019, offer an insight of a complex entrepreneurially led project-oriented organization and suggest three integrative mechanisms that describe the ambidextrous management of the interplay within and between strategy and project levels. Additionally, this research recognizes the critical role of projects also in entrepreneurial environments and suggests that the accomplishment of ambidexterity is unique in nature as it is aimed at reconciling the uniqueness of competitive propositions and that of projects within a unique entrepreneurial environment, opening avenues for more theoretical and empirical studies at the intersection of project management and entrepreneurship.